VD_FINDINFO HC / 2014 / 586 vom 14. Mai 2014 - VD Tribunal cantonal (2014)
DOMMAGE, PAIEMENT, CONTRAT DE REPRÉSENTATION EXCLUSIVE, FARDEAU DE LA PREUVE | 42 CO, 84 CO, 308 al. 1 let. a CPC (CH), 404 al. 1 CPC (CH)